KINERJA GURU DALAM PEMBELAJARAN PADA PROGRAM FULL DAY SCHOOL DI SMAN 22 MAKASSAR - Endah Ayu Kartika; Misykat Malik Ibrahim; Yusuf Tahir (Universitas Islam Negeri Alauddin Makassar, 2020)
This study discusses about the teachers performance in optimizing learning in the Full Day school program at SMAN 22 Makassar. This research was qualitative research. Data collection methods obtained through observation, interviews and documentation. The data was analyzed by reducing data, presenting data, verifying data, and validating data (triangulation). The result of the research showed that; the first was the teacher performance at SMAN 22 Makassar has improved such as planning, implementation and evaluation. The second was Full Day school at SMAN 22 Makassar about school schedules based on school rules. The third was Effective efforts to optimize learning are carried out by teachers and schools. The teacherteach the learning to the students, gave some motivation and learning methods. The school helps teachers by school rules, teaching and learning process (PBM picket) and controlled by hand master in the school.